SIKAP WARGA BELAJAR TERHADAP KETERAMPILAN DI BALAI PELATIHAN TENAGA KERJA PEKANBARU - Vegy Kamara Efita; Said Suhil Achmad; Sumardi Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:The purpose of this study was to determinethe attitudes of learning citizens towards skills at the Pekanbaru Workforce Training Center that were positive. This research is expected to be an input for citizens to study at the Pekanbaru Workforce Training Center to increase morale in conducting training. This research is descriptive with a quantitative approach that aims to describe the results of research with numbers. The sample technique in this study uses a simple random sampling technique (simple random sampling). Validity test with a critical r value of 0.361, obtained from 30 people learning. Of the 108 statement items tested, 4 invalid and 104 valid statements were found. Researchers discard invalid statements, because they do not interfere with other statements. Based on these results it canbe concluded that the attitude towards the skills given to citizens learning at the Pekanbaru Workforce Training Center is classified as good or positive, with the highest affective indicator seen from the percentage value (Y) 68%. This means that citizens learn to have a good affective attitude towards the skills activities provided by the Pekanbaru Workforce Training Center. Judging from the overall average of 3 percentage indicators (Y) of 66%, the attitudes of the learning population towards the skillsprovided to the learning population at the Pekanbaru Workforce Training Center are classified as good or positive. Key Words: Attitudes, Learning Attitudes Residents